Anatomical and functional changes in the retina in patients with Alzheimer's disease and mild cognitive impairment. Issue 7 (25th March 2020) - Szegedi, Stephan; Dal‐Bianco, Peter; Stögmann, Elisabeth; Traub‐Weidinger, Tatjana; Rainer, Michael; Masching, Andreas; Schmidl, Doreen; Werkmeister, René M.; Chua, Jacqueline; Schmetterer, Leopold; Garhöfer, Gerhard
Abstract: Purpose: There is evidence that mild cognitive impairment (MCI) or Alzheimer's disease (AD) is accompanied by alterations in the retina. The current study was performed to investigate structural and functional changes in patients with systemic neurodegenerative disease. Methods: A total of 47 patients with either MCI or AD and 43 healthy age‐ and sex‐matched control subjects were included. Inclusion criteria for MCI were abnormal memory function and a mini‐mental state examination (MMSE) score >26 points, for patients with AD a diagnosis of probable AD of mild to moderate degree and an MMSE score in the range of 20–26. Retinal blood flow was measured using a Doppler optical coherence tomography (OCT) system. Retinal vessel diameter, oxygen saturation and flicker‐induced vasodilatation were measured using a Vessel Analyzer. Retinal nerve fibre layer thickness (RNFLT) was assessed using an OCT system. Results: Global RNFLT was lower in patients compared to healthy controls (93.7 ± 12.8 µm versus 99.1 ± 9.0 µm, p = 0.02). The same was found in regards to retinal arterial blood flow, which was 9.3 ± 2.4 and 12.3 ± 3.2 μl/min in the patient and control groups, respectively (p < 0.001). Mean retinal arterial diameter was reduced in patients (76.0 ± 8.9 µm versus 80.6 ± 8.0 µm, p = 0.03). Arteriovenous difference in oxygen saturation was lower in patients (20.4 ± 5.1% versus 23.5 ± 4.0%, p < 0.01). No difference in the flicker response was observed. Conclusion: In patients with MCI and AD, arteriovenous difference in oxygen saturation, retinal blood flow and arterial vessel diameter was reduced. No difference was found in flicker response between groups. This indicates alterations in retinal oxygen metabolism in patients with neurodegenerative disease.